Z-scheme CdS–Au–BiVO4 with enhanced photocatalytic activity for organic contaminant decomposition. Issue 1 (5th December 2016) - Bao, Shenyuan; Wu, Qiangfang; Chang, Shunzhou; Tian, Baozhu; Zhang, Jinlong
Abstract : A Z-scheme heterogeneous photocatalyst CdS–Au–BiVO4 was synthesized for the first time by photo-reduction and deposition–precipitation methods. Abstract : A Z-scheme heterogeneous photocatalyst CdS–Au–BiVO4 was synthesized for the first time by photo-reduction and deposition–precipitation methods. The microstructures and optical properties of the as-prepared samples were investigated by means of scanning electron microscopy (SEM), field emission scanning electron microscopy (FE-SEM), high resolution transmission electron microscopy (HR-TEM), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), and UV-vis diffuse reflectance spectroscopy (DRS). Due to the oriented accumulation of electrons on the {010} facets of BiVO4 crystals, Au nanoparticles were successfully anchored on the {010} facets of BiVO4 crystals via the photo-reduction process. CdS was further selectively deposited on the surface of Au nanoparticles, benefitting from the strong S–Au interaction. Photocatalytic degradations of tetracycline and Rhodamine B indicated that CdS–Au–BiVO4 exhibits much higher photocatalytic activity than BiVO4, Au–BiVO4, and CdS–BiVO4 . Radical trapping experiments confirmed that in the case of CdS–Au–BiVO4, the main reactive species responsible for organic contaminant degradation are h +, ˙OH, and ˙O2 −, while only h + can be produced in the case of CdS–BiVO4 . Based on the photoelectrochemical analysis and radical trapping experiments, it can be deduced that the Z-scheme structure of CdS–Au–BiVO4 not only decreases the recombination rate of photo-generated carriers but also makes the holes and electrons keep a higher redox ability.